Quality Analysis of Various National and International Brands of Glimepirides Available in Pakistan - Salman Ahmed, Imran Suheryani, Muhammad Ali Ghoto, Shaib Muhammad, Ubed-Ur-Rehman Mughal, Zeeshan Ahmed, Shayan Ahmed, Razia Sultana, Rabeia, Jameela Jamali, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The primary focus of this research is to ascertain that these different generic drug products from national and multinational companies competing in the local market are equivalent in quality. Material and Methods: A comparative quality analysis was executed on national and multinational brands of glimepiride tablets obtained from local pharmacies of Hyderabad. A cumulative of 6 glimepiride brands were selected and internationally accepted in-vitro tests were carried out at Industrial pharmacy laboratory of Department of Pharmaceutics, Faculty of Pharmacy, University of Sindh, Jamshoro, during time period August 2021 to August 2022 to compare with Pharmacopoeia standards. Results: All the drug products (Glimepiride tablets) obtained from local market were meeting the standards laid by BP for tests of weight uniformity, diameter, thickness, hardness, friability, disintegration, and content uniformity/assay. Conclusion: Every generic of glimepiride tablets from various local and multinational manufacturers are pharmaceutical equivalents and can be prescribed interchangeably. Keywords: National, International, Brand, Glimepiride, Quality, Pharmaceutical Equivalents